2005
DOI: 10.1243/095440605x31526
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Failure Analysis of Austenitic Nuclear Pipelines against Stress Corrosion Cracking

Abstract: Stress corrosion cracking (SCC) is an important degradation mechanism to be considered for failure assessment of nuclear piping components made of austenitic steels. In this paper, an attempt has been made to compute the failure probabilities of a piping component against SCC with time using Monte Carlo simulation (MCS) technique. The initiation and propagation stages of stress corrosion cracks are modelled using the general methodology recommended in PRAISE modified by using the recommendations given by ASM f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…For AISI 304 austenitic stainless steel, F has a mean of 2·551 and standard deviation of 0·4269, and G = 1·3447 (Harris et al 1992). From parametric studies carried out, a value of 5% coefficient of variation of log(v 1 ) was found to be critical to life of piping component (Priya et al 2005), and hence this value is used in this study. The procedure followed for transition from initiation to fracture mechanics crack growth rate in the present study is (Anoop et al 2008):…”
Section: 1dmentioning
confidence: 99%
See 3 more Smart Citations
“…For AISI 304 austenitic stainless steel, F has a mean of 2·551 and standard deviation of 0·4269, and G = 1·3447 (Harris et al 1992). From parametric studies carried out, a value of 5% coefficient of variation of log(v 1 ) was found to be critical to life of piping component (Priya et al 2005), and hence this value is used in this study. The procedure followed for transition from initiation to fracture mechanics crack growth rate in the present study is (Anoop et al 2008):…”
Section: 1dmentioning
confidence: 99%
“…For AISI 304 austenitic stainless steel, C 12 = 0·8192, C 13 = 0·03621 and C 15 = 1·7935, mean value of C 14 = −3·1671 and standard deviation of C 14 = 0·7260 (Harris et al 1992). From a probabilistic failure analysis of austenitic nuclear pipe against SCC, Priya et al (2005) inferred that expressions given in PRAISE for computation of stress intensity factors for modelling crack propagation need modification. In Priya et al (2005), this modification has been introduced by using well-accepted expressions given in ASM, and with modified PRAISE approach, stochastic propagation of stress corrosion cracks with time has been studied.…”
Section: 1dmentioning
confidence: 99%
See 2 more Smart Citations
“…Rahman (Rahman S. 1997) has developed another computer code named PSQUIRT (probabilistic see page quantification of upsets in reactor tubes) to determine the probability of leak age of piping made of stainless steel and carbon steel subjected to intergranular stress corrosion cracking (IGSCC) and corrosion fatigue. Failure probabilities of a piping component subjected to SCC was computed in (Priya C et al, 2005and Guedri et al, 2009a, 2009b) using a Monte Carlo simulation (MCS) technique.…”
Section: Introductionmentioning
confidence: 99%